2001
DOI: 10.1126/science.1060612
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Cognate Transfer RNA by the 30 S Ribosomal Subunit

Abstract: Crystal structures of the 30S ribosomal subunit in complex with messenger RNA and cognate transfer RNA in the A site, both in the presence and absence of the antibiotic paromomycin, have been solved at between 3.1 and 3.3 angstroms resolution. Cognate transfer RNA (tRNA) binding induces global domain movements of the 30S subunit and changes in the conformation of the universally conserved and essential bases A1492, A1493, and G530 of 16S RNA. These bases interact intimately with the minor groove of the first t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

67
1,211
7
32

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,121 publications
(1,334 citation statements)
references
References 47 publications
67
1,211
7
32
Order By: Relevance
“…Co‐crystal structures of a variety of bound aminoglycosides have been published, including with streptomycin ( 31 , PDB ID: 1FJG),110 spectinomycin ( 32 , PDB ID: 1FJG),110 hygromycin B ( 33 , PDB ID: 1HNZ),97 neomycin B ( 34 , PDB ID: 4V52),111 paromomycin ( 35 , PDB ID: 1FJG, 1IBK),110, 112 tobramycin ( 36 , PDB ID: 1LC4),113 and kanamycin A ( 37 , PDB ID: 2ESI) 109…”
Section: Protein Synthesis Inhibitorsmentioning
confidence: 99%
“…Co‐crystal structures of a variety of bound aminoglycosides have been published, including with streptomycin ( 31 , PDB ID: 1FJG),110 spectinomycin ( 32 , PDB ID: 1FJG),110 hygromycin B ( 33 , PDB ID: 1HNZ),97 neomycin B ( 34 , PDB ID: 4V52),111 paromomycin ( 35 , PDB ID: 1FJG, 1IBK),110, 112 tobramycin ( 36 , PDB ID: 1LC4),113 and kanamycin A ( 37 , PDB ID: 2ESI) 109…”
Section: Protein Synthesis Inhibitorsmentioning
confidence: 99%
“…Three universally conserved nucleotides in the E. coli decoding site-G530, A1492, and A1493-interact with the codon-anticodon helix to monitor the accuracy of base pairing (Cate et al 1999;Ogle et al 2001;Yusupov et al 2001). The prokaryotic decoding site is also the target for many aminoglycosides antibiotics, which interfere with translational fidelity (Carter et al 2000).…”
Section: Mutagenesis Of Nucleotides In the Yeast 18s Rrna Decoding Sitementioning
confidence: 99%
“…Structural and chemical protection studies have shown that aminoglycosides bind to specific nucleotides in the decoding site of 16S rRNA in bacteria (Fig. 1A), where they induce a conformational change similar to the transition that occurs upon cognate tRNA binding (Purohit and Stern 1994;Ogle et al 2001;Ogle and Ramakrishnan 2005). As a result, aminoglycosides interfere with bacterial protein synthesis by facilitating amino acid misincorporation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(B) The SPF specific region of RF2 was mapped exclusively to rRNA from one of the two ribosomal subunits. The cleavages in E. coli rRNA derived from hydroxyl radicals generated from near 205 SPF 207 (Cys 204 or 209 on modified RF2s with unique cysteines have been mapped here on the rRNA structures derived from X-ray structures of 16S rRNA from Thermus thermophilus [36]. The release factor at the ribosomal active centre 596 npg bromoacetamidobenzyl)-EDTA (BABE) was attached to the specific cysteine, newly engineered into the protein so that Fenton chemistry could be used to activate the generation of free hydroxyl radicals at the site.…”
Section: Is the Decoding Rf More Promiscuous Than A Trna In Its Contamentioning
confidence: 99%